2015
DOI: 10.1523/jneurosci.0490-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Role of Striatal Cholinergic Interneurons in Set-Shifting in the Rat

Abstract: The ability to change strategies in different contexts is a form of behavioral flexibility that is crucial for adaptive behavior. The striatum has been shown to contribute to certain forms of behavioral flexibility such as reversal learning. Here we report on the contribution of striatal cholinergic interneurons-a key element in the striatal neuronal circuit-to strategy set-shifting in which an attentional shift from one stimulus dimension to another is required. We made lesions of rat cholinergic interneurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
117
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 51 publications
12
117
0
Order By: Relevance
“…Individual DMS CINs represented state from the start to the end of the trials within each block. The finding that CINs code state is consistent with evidence that interference with cholinergic function in the striatum often causes problems with flexible behavior (Tzavos et al, 2004;Ragozzino et al, 2009;Okada et al, 2014;Aoki et al, 2015) and with very specific evidence that this reflects a role for DMS CINs in integrating new learning with old without interference (Bradfield et al, 2013). Bradfield et al…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Individual DMS CINs represented state from the start to the end of the trials within each block. The finding that CINs code state is consistent with evidence that interference with cholinergic function in the striatum often causes problems with flexible behavior (Tzavos et al, 2004;Ragozzino et al, 2009;Okada et al, 2014;Aoki et al, 2015) and with very specific evidence that this reflects a role for DMS CINs in integrating new learning with old without interference (Bradfield et al, 2013). Bradfield et al…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with this proposal, interference with cholinergic function in the striatum often causes problems with flexible behavior (Tzavos et al, 2004;Ragozzino et al, 2009;Okada et al, 2014;Aoki et al, 2015). In one such study, Bradfield et al, 2013 used a series of well controlled behavioral tasks to demonstrate that interfering with CIN activity in the posterior dorsomedial striatum (DMS) specifically results in confusion between old learning and new after response-outcome contingencies have been changed.…”
Section: Introductionmentioning
confidence: 91%
“…For example, VS inactivation impairs behavioral performance during rule switching (Floresco et al, 2006), whereas VS cholinergic interneurons have been shown to play an important role in rule switching (Aoki et al, 2015). A recent comprehensive review of VS function also proposes that VS serves to refine action selection dynamically by incorporating multiple sources of information including, but not limited to, reward (Floresco, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Without a functioning mDS, rats demonstrated impairment in the formation of sets and the maintenance of new sets when shifts in responses were required(Lindgren et al, 2013, Bissonette and Roesch, 2015c). Recent work has even uncovered a critical role for cholinergic interneurons of the medial and ventral striatum in shifting between rule based responses in the rat(Aoki et al, 2015) and ventral striatal neurons showing outcome representations while animals learn new tasks(Atallah et al, 2014). However, our understanding of how dorsal striatum presumably uses and interprets signals from PFC about how and when to shift between rule based response strategies is very limited.…”
Section: Neurophysiology Of Rule Shifting In the Striatummentioning
confidence: 99%